Manajemen Sumber Daya Manusia di Lembaga Pendidikan Islam di Indonesia - Amaliyah, Rusda; Rindaningsih, Ida (Lembaga Yasin AlSys, 2025)
Human Resource Management (HRM) plays an important role in supporting the success of Islamic educational institutions, such as madrasahs and Islamic boarding schools. This study aims to explore the concepts, strategies, and challenges in HRM management in Islamic educational institutions, by integrating Islamic values ​​and modern management approaches. The method used is a literature review, analyzing various literature related to aspects of HR planning, training, development, and evaluation. The findings show that structured and sustainable HRM planning can improve organizational effectiveness, while competency-based training and development not only improve the professional capacity of educators but also strengthen Islamic character. In addition, job satisfaction of educators is influenced by decent compensation, a supportive work environment, and an organizational culture based on the values ​​of justice and trustworthiness. The integration of Islamic values ​​such as justice, trustworthiness, and deliberation with modern management practices has proven effective in creating a productive and harmonious work environment. This study recommends the implementation of a technology-based HRM management system, ongoing training programs, and further research on the impact of Islamic values ​​on HRM effectiveness. The results of this study are expected to contribute to improving the quality of HRM management in Islamic educational institutions and support the achievement of their vision in producing a generation with noble character and global competitiveness.